Contacting gamete donors to facilitate diagnostic genetic testing for the donor-conceived child: what are the rights and obligations of gamete donors in these cases? A response to Horton et al. Issue 3 (3rd September 2019) - Frith, Lucy
Abstract : In their paper Horton et al argue that it is acceptable to contact an anonymous egg-donor to facilitate diagnostic genetic testing for the donor conceived child, despite the donor, 'indicating on a historical consent form that she did not wish to take part in future research, and that she did not wish to be informed if she was found to be a carrier of a "harmful inherited condition"'. There are a number of claims embedded in Horton et al 's position that it is acceptable to contact the donor and request that she at least think about participating in genetic testing. In this response. I will go through their main claims and argue that the area of genomic medicine does not justify exceptions to general consent conditions as the authors suppose and conclude that the donor should not be contacted. I will then go on to suggest a policy change that would address Horton et al 's concerns but would not involve over-riding any previously expressed wishes.